∫(-π/4->π/4) x/(1+sinx) dx
=∫(-π/4->0) x/(1+sinx) dx + ∫(0->π/4) x/(1+sinx) dx
u=-x
=∫(π/4->0) u/(1-sinu) du + ∫(0->π/4) x/(1+sinx) dx
=-∫(0->π/4) x/(1-sinx) dx + ∫(0->π/4) x/(1+sinx) dx
=∫(0->π/4) x[ 1/(1+sinx) -1/(1-sinx)] dx
=-2∫(0->π/4) xsinx/(cosx)^2 dx
=-2∫(0->π/4) xd(1/cosx)
=-2[x/cosx]|(0->π/4) +2∫(0->π/4) (1/cosx) dx
= -(√2/2)π + 2[ln|secx+tanx|]|(0->π/4)
= -(√2/2)π + 2ln(1+√2)
=∫(-π/4->0) x/(1+sinx) dx + ∫(0->π/4) x/(1+sinx) dx
u=-x
=∫(π/4->0) u/(1-sinu) du + ∫(0->π/4) x/(1+sinx) dx
=-∫(0->π/4) x/(1-sinx) dx + ∫(0->π/4) x/(1+sinx) dx
=∫(0->π/4) x[ 1/(1+sinx) -1/(1-sinx)] dx
=-2∫(0->π/4) xsinx/(cosx)^2 dx
=-2∫(0->π/4) xd(1/cosx)
=-2[x/cosx]|(0->π/4) +2∫(0->π/4) (1/cosx) dx
= -(√2/2)π + 2[ln|secx+tanx|]|(0->π/4)
= -(√2/2)π + 2ln(1+√2)